Oportunidades de economía circular con residuos del cultivo de maíz (Zea Mays) en la zona norte de la provincia de Los Ríos - Zambrano Sornoza, Cindy Jamileth (2021)
The present study was carried out in the northern area of the Los Ríos province in the Quinsaloma cantons; Mocache; Quevedo; Puebloviejo and Windows. Corn is one of the oldest known food grains and due to its benefits, it has become the most important crop among cereals worldwide. Agricultural waste entails serious problems due to the inadequate treatment, use of resources, or final disposal of waste, as well as the generation of waste, which makes a change in style essential by implementing a circular economy model as a profitable and sustainable strategy. in the long term, which allows establishing a balance between economic growth, social welfare and the use of resources. In order to propose circular economy opportunities with residues from the corn crop. Stop which the descriptive and analytical research was implemented through a confidence level of 95% by applying a questionnaire with quantitative and qualitative variables and proceeded to perform the univariate analysis where the Chi-square test was used. to evaluate the relationships of the response variables with the predictors. It was determined that through the characterization of the waste, inorganic waste was found with a total of 20.54 tons / year and organic waste with a total of 0.722 tons / year of which this amount of waste is an estimate as stated by small farmers. The producers determined as adaptable the vermicomposting project that deals with an ecotechnological process that occurs due to the decomposition of organic waste, the action of worms and the presence of microorganisms and at the same time it is a project that has no cost. Keywords: Agricultural associations, Sustainable practices, Agricultural solid waste, Reuse, Circular economy.